Ta'tsiiru Kholfiyyati al-Tholabah al-Dirosiyyah wa Kafaatihim fi Ta'allumi al-Lughoh al-Arobiyyah lada Tholabati al-Madaaris al-Tsaanawiyyah al-Islaamiyyah bi Malang - Shofil Fikri; Hadi Nurdi Hamzah (Lugawiyyat, 2022)
Learning Arabic at Madrasah Aliyah in the city of Malang faces various difficulties, including: (1) Non-linearity in student education. Students from Islamic Junior High School (MTs) do not always continue their studies to Islamic Senior High School (MA) and similarly students from Junior High School (SMP) do not always continue their studies to Senior High School (SMA). (2) The second problem is the language competence of each student which is also an important thing in the Arabic learning process. This research is very important to do to find out the relationship between students' background and their learning ability. The two researchers used quantitative research to determine the effect of students' background and competence on the motivation to learn Arabic among Islamic Senior High School (MA) students in Malang. The results of this study are R = 0.317 R Table 0.113 which means it has a weak correlation and the results of multiple regression tests are obtained by chi square 0.100, which means that students' background (X1) and competence (X2) have an effect = 1.00% on motivation to learn Arabic in Indonesia among students of Islamic Senior High School Malang (Y). There are other factors that affect the motivation to learn Arabic in Madrasah Aliyah students except the academic background and proficiency of students by 99.00%, and this result is greater than the influence of background and language proficiency of students.